Impending Collision Judgment from an Egocentric Perspective in Real and Virtual Environments: A Review. (September 2019) - Feldstein, llja T.
The human egocentric perception of approaching objects and the related perceptual processes have been of interest to researchers for several decades. This article gives a literature review on numerous studies that investigated the phenomenon when an object approaches an observer (or the other way around) with the goal to single out factors that influence the perceptual process. A taxonomy of metrics is followed by a breakdown of different experimental measurement methods. Thereinafter, potential factors affecting the judgment of approaching objects are compiled and debated while divided into human factors (e.g., gender, age, and driving experience), compositional factors (e.g., approaching velocity, spatial distance, and observation time), and technical factors (e.g., field of view, stereoscopy, and display contrast). Experimental findings are collated, juxtaposed, and critically discussed. With virtual reality devices having taken a tremendous developmental leap forward in the past few years, they have been able to gain ground in experimental research. Therefore, special attention in this article is also given to the perception of approaching objects in virtual environments and put in contrast to the perception in reality.